Once a laird [large type] - Putney, Mary Jo (Putney, Mary Jo. Rogues redeemed, 2021)
After the death of his fiancée, Kai Ramsey left Scotland to roam distant lands. Having escaped certain death after being imprisoned as a spy during the Napoleonic War, Ramsay has lived on the edge of danger for years - but everything changes when a letter arrives for him from Scotland. Signy Matheson has dedicated her life to the people of Scotland's remote Thorsay Islands. With a fiery spirit and agile mind, she is a faithful ally to the aging laird. But now their leader is near death, and Signy must summon his successor at once. It's time for Kai Ramsey to come home. When Ramsay returns to Thorsay, he's shocked to find that Signy has blossomed into an alluring beauty and a force to be reckoned with. Their complicated past interferes with their unspoken desire as they work together for their people. Until a wild storm sparks first passion, then unexpected danger when a treasure trove left by their ancestors comes to light.